2021
DOI: 10.1002/cam4.4402
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a prognostic immune‐related signature for small cell lung cancer

Abstract: Purpose As a subgroup of lung cancer, small cell lung cancer (SCLC) is characterized by a short tumor doubling time, high rates of early occurred distant cancer spread, and poor outcomes. Despite its exquisite sensitivity to chemotherapy and radiotherapy, acquired drug resistance and tumor progression are typical. This study aimed to develop a robust signature based on immune‐related genes to predict the outcome of patients with SCLC. Methods The expression data of 77 SCLC patients from George's cohort were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In Checkmate032, a study assessing nivolumab alone or nivolumab and ipilimumab in recurrent ES-SCLC, both PD-L1 status and TMB were assessed as predictive biomarkers with no evidence of an association between PD-L1 expression and ORR [ 12 ]. In addition to biomarkers, there have been early investigations into identifying SCLC subtypes based on transcription factor expression [ 38 ], as well as varying immune signatures [ 39 ]. However, these models are not yet validated [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Checkmate032, a study assessing nivolumab alone or nivolumab and ipilimumab in recurrent ES-SCLC, both PD-L1 status and TMB were assessed as predictive biomarkers with no evidence of an association between PD-L1 expression and ORR [ 12 ]. In addition to biomarkers, there have been early investigations into identifying SCLC subtypes based on transcription factor expression [ 38 ], as well as varying immune signatures [ 39 ]. However, these models are not yet validated [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer, the leading cause of cancer death throughout the world, claims the lives of more than 350 people every day [ 19 ]. During the last decade, although there was a steep decline in lung cancer incidence for advanced cases based on the changes in cancer screening and treatment, only 15% of patients with NSCLC can live beyond five years [ 20 ]. LUSC, the most common pathological subtype of NSCLC, known for its high tumor heterogeneity, showed a significant therapeutic difference in immunotherapy response rate [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…95,98 A study of SCLC human tissue samples showed considerable overlap between the SCLC-I phenotype and tumours with YAP1 transcriptional predominance, and indicated that an inflamed transcriptional signature correlated inversely with expression of neuroendocrine markers. 102 Current evidence also suggests that SCLC-I are associated with longer survival than noninflamed SCLC, [101][102][103] possibly due to immune interactions. Interestingly, retrospective analysis of a small number of tissue samples from patients who responded to immune checkpoint blockade during the IMPower133 trial showed a trend toward better response in tumours with the "SCLC-I" phenotype, but included too few patients to draw definitive conclusions.…”
Section: S M a L L -C E L L C A R C I N O M Amentioning
confidence: 99%